KEPEMIMPINAN MULTIKULTURAL: (Studi Empiris pada Pesantren Nurul Hidayah Masaran Palengaan) - Ghani, Abd (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah IAI Miftahul Ulum, 2024)
This study examines the form of leadership. The leadership in question is multicultural leadership. Conceptually, a leader is a leader who is able to anticipate, dream of, apply the concept of flexibility, think strategically and work to initiate and bring about change in order to create a better future for the organization. This research uses a qualitative approach, by making educational institutions as the setting. In his research, he concluded that decision making in multicultural leadership that rubs against socio-cultural factors often sparks the fire between groups. For this reason, a leader who understands the concept of multicultural leadership is required to be a communication bridge between employees. Multicultural leaders can apply the principles of justice and truth by drawing policies based on needs, not just the desires of one or two parties. Awareness of the facts of differences needs to be addressed and managed by a leadership concept that is able to synergize each diversity into a beauty.